2008
DOI: 10.1097/fjc.0b013e31817dd013
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Effects of the IKr Agonist NS3623 on Cardiac Electrophysiology of the Guinea Pig

Abstract: The long QT syndrome is characterized by a prolongation of the QT interval measured on the surface electrocardiogram. Prolonging the QT interval increases the risk of dangerous ventricular fibrillations, eventually leading to sudden cardiac death. Pharmacologically induced QT interval prolongations are most often caused by antagonizing effects on the repolarizing cardiac current called IKr. In humans IKr is mediated by the human ether-a-go-go related gene (hERG) potassium channel. We recently presented NS3623,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…In this context, dofetilide treatment continued to block the channel but at a somewhat higher IC 50 value (58 nM) compared with dofetilide treatment alone (11 nM). Hansen et al (2008) also reported that in vivo treatment of guinea pigs with NS3623 produced a reversal of E4031-induced prolongation of the QT interval. In the absence of pharmacologic blockade of hERG1, Patel and Antzelevitch (2008) reported that the hERG1 activator PD118057 abbreviated the QT interval but increased transmural dispersion of repolarization.…”
Section: Downloaded Frommentioning
confidence: 99%
“…In this context, dofetilide treatment continued to block the channel but at a somewhat higher IC 50 value (58 nM) compared with dofetilide treatment alone (11 nM). Hansen et al (2008) also reported that in vivo treatment of guinea pigs with NS3623 produced a reversal of E4031-induced prolongation of the QT interval. In the absence of pharmacologic blockade of hERG1, Patel and Antzelevitch (2008) reported that the hERG1 activator PD118057 abbreviated the QT interval but increased transmural dispersion of repolarization.…”
Section: Downloaded Frommentioning
confidence: 99%
“…In line with theoretical considerations, the measured and corrected QT interval was reduced in both conditions. Furthermore, NS3623 reverses drug-induced QT prolongation (171). In rabbits, NS1643 has demonstrated antiarrhythmic properties in a pharmacological and nonpharmacological model for ventricular fibrillation.…”
Section: B Strategies For Treatment Of Vfmentioning
confidence: 99%
“…It was therefore expected that hERG1 channel agonists could decrease the proclivity for these biomarkers, and this assumption has been confirmed in a number of different experimental settings. hERG1 channel agonists decrease dispersion and triangulation, prevent bradypacing and pharmacological-induced arrhythmias, shorten QT intervals in vivo, and directly protect against arrhythmias (Kang et al, 2005;Hansen et al, 2007Hansen et al, , 2008Diness et al, 2008Diness et al, , 2009). However, hERG1 agonists can also be proarrhythmic under certain settings (Larsen et al, 2008;Lu et al, 2008), placing obvious restrictions on their potential therapeutic use.…”
Section: Herg1 Kmentioning
confidence: 99%